Ancillary palm oil fuel ash (POFA) in sequencing batch reactor for enhancing recalcitrant pollutants removal from domestic wastewater. (February 2021) - Lyn, Chan Wy; Bashir, Mohammed JK.; Wong, Ling Yong; Lim, Jun Wei; Sethupathi, Sumathi; Ng, Choon Aun
Abstract: Domestic wastewater has been generated massively along with rapid growth of population and economic. Biological treatment using sequencing batch reactor (SBR) augmented with palm oil fuel ash (POFA) was investigated for the first time. The performance of POFA in enhancing biological treatment of wastewater has not been tested. The porosity property of POFA can improve SBR efficiency by promoting growth of mixed liquor suspended solids (MLSS) and formation of larger flocs for settling and facilitating attachment of microorganisms and pollutants onto POFA surfaces. The properties of POFA were tested to identify morphological properties, particle size, surface area, chemical compositions. Four SBRs, namely SBR1, SBR2, SBR3 and SBR4 were provided with aeration rate of 1, 2, 3 and 4 L/min, respectively. Each reactor was augmented with different dosages of POFA. Optimum aeration rate and POFA concentration were identified by the performance of SBRs in removing chemical oxygen demand (COD), ammoniacal nitrogen (NH3 –N) and colour from domestic wastewater. The results showed the most efficient COD (97.8%), NH3 –N (99.4%) and colour (98.8%) removals were achieved at optimum POFA concentration of 4 g/L in SBR and aeration rate of 1 L/min. The study also found that higher aeration rate would contribute to the smaller specific size of flocs and decrease the pollutant removal efficiency. Graphical abstract: Image 1 Highlights: Palm oil fuel ash augmented with sequencing batch reactor was adopted for domestic wastewater treatment. POFA was able to improve SBR efficiency by promoting growth of mixed liquor suspended solids (MLSS). Higher aeration rate contributed to smaller specific size of flocs and lower pollutant removal efficiency. Most efficient COD, NH3 –N and colour removals were achieved at 97.8%, 99.4% and 98.8% respectively.